CODE-MIXING AND CODE-SWITCHING ANALYSIS IN BOY WILLIAM YOUTUBE CHANNEL: GELEDAH ISI LEMARI DI DALAMNYA TAS BRANDED SEMUA - dewi, Ni Luh Desy Suari; Elkie Shafira, Putu Mayra; Kusuma Wardhani, Ni Putu Anggie; Novi Utami, Gek Wulan; Prajamukti Wardhana, I Gede Neil (Linguistik : Jurnal Bahasa dan Sastra, 2023)
Young generations, usually speak two or more languages for their communication (Sukrisna, 2019). Based on this phenomenon, we can say that our young generations use code-switching and code-mixing in their utterances. It is interesting to discuss the types of code choices used and to know the reasons to switch or mix from one language to another. A qualitative method was used to gather and analyze explanatory data. The data were analyzed by using Hoffman's theory which classified code choice into code-switching and code-mixing and also categorized the reasons for using code choice into seven reasons. The research can be concluded that types of code-switching used in â€œBoy William Youtube Channel: Geledah Isi Lemari Di Dalamnya Tas Branded Semua!â€ are Intra-sentential Switching, Inter-sentential Switching, and Tag Switching. Meanwhile, types of code-mixing found are Intra-sentential Mixing and Intra-lexical Code-mixing. There are also found several reasons for using Code-mixing and Code-switching in conversation. The reasons are talking about a particular topic, being emphatic about something (expressing solidarity), interjection (inserting sentence fillers or sentence connectors), repetition used for clarification, the intention of clarifying the speech content for the interlocutor, and expressing group identity.Keywords: Code-switching, Code-mixing, Sociolinguistics